Nonlinear normalized fractional electroosmotic spacelike fluid model - Talat Körpinar; Zeliha Körpinar; Ali Akgül; Qasem Al-Mdallal (International Journal of Thermofluids)
In this paper, we present optical recursively fractional SKμ−electroosmotic fractional recursivelySKμ−energy. Also, we have spacelike microfluidicsfractional SKμ− electroosmotic recursively tension energy. Moreover, we construct main Katugampola recursive-normal hyperbolic fractional KFα−tension field in hyperbolic space. Finally, we characterize spacelike radiative recursively fractional SKμ− phase in hyperbolic space.